Technical guidelines on mechanized direct seeding combined with fertilizer deep placement in rice production in the Mekong River Delta - Nguyen Van Hung; Nguyen Van Hieu; Nguyen Ngoc Hoang; Nguyen Hong Thien; Nguyen Huu Diem Ha; Pham Thi Minh Hieu; Tran Thi Kim Thuy; Le Nhut Tao; Nguyen Thuy Kieu Tien; Tran Ngoc Thach; Dinh Thi Kim Dung (2024)
This document provides comprehensive technical guidelines for mechanized direct seeding combined with fertilizer deep placement in rice production within the Mekong River Delta. The focus is on promoting high-quality and low-emission rice production in the region.